Resolution of Abnormal Gonadotropin Secretion After Surgical Cure in Men With ACTH-Dependent Cushing Syndrome - Shekhar, Skand (J Endocr Soc, 2021)
Background: Hypothalamic-pituitary-gonadal (HPG) dysfunction is known to occur in male patients with Cushing Syndrome (CS) but the underlying mechanisms of HPG dysfunction remain unclear. We performed frequent blood sampling and GnRH stimulation tests to assess gonadotropin secretion in males before and after surgical cure of CS. Methods: We evaluated eight males age 32.5±12 years (mean ± SD) enrolled for surgical cure of ACTH-dependent CS at a tertiary care research center. Urinary free cortisol (UFC) was measured before and after surgery. Blood was sampled every 20 minutes for 24-hours with measurement of LH and FSH, before and 2 weeks to 160 weeks (median 80 weeks) after surgery. Patients received 100 μg of gonadotropin releasing hormone (GnRH) iv with measurement of LH and FSH at 0, 10 and 20 min before and 15, 30, 45, 60, 120 and 180 min after administration. Non-normative data was log-transformed before analysis using paired two-tail t-tests. A p-value of <0.05 was considered significant. Gonadotropin values are expressed in U/L as equivalents of the 2(nd) International Preparation of human menopausal gonadotropins with normal adult male ranges of 6-26 and 5-25 IU/L for LH and FSH, respectively. Results: Mean UFC was elevated ~ 6 times above the upper normal limit before surgery and returned to the reference range after surgery. 24-hour LH rose from 7.82 ± 1.48 preoperatively to 13.07 ± 2.96 IU/L (mean ± sem) after surgery (p=0.026) while mean FSH was unchanged (8.48 ± 1.51 vs 6.92 ± 1.29, p=0.37). LH pulse frequency, a marker of pulsatile GnRH secretion, recovered from a subnormal value of 6.88 ± 0.55 pulses/24 hr before to 12.13 ± 0.72 pulses/24 hr after surgery (p<0.0001) while LH pulse amplitude did not change (6.47 ± 1.21 vs 4.76 ± 0.88 IU/L, p=0.21). In response to GnRH there was a robust increase in LH that was not affected by curative surgery for CS (27.0 ± 7.2 vs 21.2 ± 7.6 IU/L; p=0.14) as was also the case for FSH (3.7 ± 1.2 vs 2.3 ± 0.5 IU/L; p=0.48), consistent with the absence of an effect of CS on gonadotroph responsiveness to LHRH. Conclusion: In men with Cushing Syndrome, hypogonadism is associated with inhibition of endogenous GnRH secretion but preservation of the pituitary response to GnRH. Hypothalamic suppression of the HPG axis is reversible after cure of CS.